2022
DOI: 10.21608/ejnhs.2022.251410
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Footprint Knowledge and Calculation among Nursing Students

Abstract: Background: Nursing students as future health leaders to advocate for a greener planet, have a significant responsibility in mitigating climate change and reducing humanity' carbon footprint (CF). While the CF per capita among nursing students is unknown, and whether they are well knowledgeable about effective measures for reducing CF. Aim: Assess carbon footprint knowledge and calculation among nursing students Methodology: A descriptive-analytic research design was applied for A stratified simple random samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
1
1
Order By: Relevance
“…The findings of the study contrast with those of Moselhy M et al, (2022) (35) , who discovered that the majority of the observable students were male. More than half of them were revealed to be residing in rural areas at a middle socioeconomic level in other research conducted by Ibrahim et al, (2018) (8) and Ghazy Fathy (2023).…”
Section: Discussioncontrasting
confidence: 99%
“…The findings of the study contrast with those of Moselhy M et al, (2022) (35) , who discovered that the majority of the observable students were male. More than half of them were revealed to be residing in rural areas at a middle socioeconomic level in other research conducted by Ibrahim et al, (2018) (8) and Ghazy Fathy (2023).…”
Section: Discussioncontrasting
confidence: 99%
“…5.2.1 | The state of the planet is affecting human health and wellbeingStudies showed mixed results regarding nursing students' awareness of the consequences of climate change to human health Felicilda-Reynaldo et al (2018). found that only half of their participants in four Arab countries thought climate change was something negative, whilstMoselhy et al (2022) found a lack of awareness about the concept of carbon footprint in two thirds of their Egypt student participants. Similar findings byÖrs (2022) suggest that the vast majority of students at a Turkish university (92.8%) did not have adequate environmental knowledge when assessed based on how many right answers they gave to questions on environmental matters.…”
mentioning
confidence: 99%